Synthesis of 3-Oxo-4-aza-5β-System from (25R)-3-Oxo-A-Norspirostane - Yadav, M.R.; Ganesh, M.M.; Giridhar, R.; Kumar, Manoj (Asian Journal of Chemistry, 2016)
Azasteroids possess a wide range of biological activities. Neuromuscular blocking agents belonging to the class of azasteroids arc bisquaternary ammonium compounds. On account of the importance of azosteroids, it was planned to synthesize a compound (4) having one nitrogen at position-3 in ring-A and the other nitrogen attached to the C-16 position. Diosgenin (12), a cheap precursor of basic steroid skeleton was used as the starting material, Diosgenin (12) was converted to (25R)-4-hydroxy-4-spirosten-3-one (13) by the known method. Benzilic acid rearrangement of the enol (13) offered the t-alcohol (14) which was oxidized to the ketone (15), thus reducing the size of ring-A. Oximation and Beckmann rearrangement of the oxime (16) offered lactam (17). Although, nitrogen at position-3 in ring-A could not be introduced by the designed scheme, it provided an efficient method for the preparation of 3-oxo-4-aza-5β-steroids from a cheap starting material like diosgenin (12).